BS EN ISO 20685-2. Ergonomics. 3-D scanning methodologies for internationally compatible anthropometric databases. Part 2. Evaluation protocol of surface shape and repeatability of relative landmark positions (9th September 2022) - British Standards Institution,
No abstract available